Metabolic Reprogramming in Adipose Tissue During Cancer Cachexia - Weber, Bahar Zehra Camurdanoglu; Arabaci, Dilsad H.; Kir, Serkan (Frontiers in Oncology, 2022)
Cancer cachexia is a disorder of energy balance characterized by the wasting of adipose tissue and skeletal muscle resulting in severe weight loss with profound influence on morbidity and mortality. Treatment options for cancer cachexia are still limited. This multifactorial syndrome is associated with changes in several metabolic pathways in adipose tissue which is affected early in the course of cachexia. Adipose depots are involved in energy storage and consumption as well as endocrine functions. In this mini review, we discuss the metabolic reprogramming in all three types of adipose tissues – white, brown, and beige – under the influence of the tumor macro-environment. Alterations in adipose tissue lipolysis, lipogenesis, inflammation and adaptive thermogenesis of beige/brown adipocytes are highlighted. Energy-wasting circuits in adipose tissue impacts whole-body metabolism and particularly skeletal muscle. Targeting of key molecular players involved in the metabolic reprogramming may aid in the development of new treatment strategies for cancer cachexia.